2015
DOI: 10.1021/acs.macromol.5b00129
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Signature of Two Distinct H-Aggregate Species in Poly(3-hexylthiophene)

Abstract: In an endeavor to correlate the optoelectronic properties of π-conjugated polymers with their structural properties, we investigated the aggregation of P3HT in THF solution within a temperature range from 300 to 5 K. By detailed steady-state, site-selective, and time-resolved fluorescence spectroscopy combined with Franck–Condon analyses, we show that below a certain transition temperature (265 K) aggregates are formed that prevail in different polymorphs. At 5 K, we can spectroscopically identify two H-type a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
120
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(134 citation statements)
references
References 53 publications
13
120
1
Order By: Relevance
“…In the same ways as in polymers, we observe that aggregation proceeds in a three-step process, where the actual process of dimer/aggregate formation is preceded by planarization of the molecular backbone, and followed by further optimization of the aggregate geometry. 13,24 It appears that the process of planarization is required a priori to enable the intermolecular interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same ways as in polymers, we observe that aggregation proceeds in a three-step process, where the actual process of dimer/aggregate formation is preceded by planarization of the molecular backbone, and followed by further optimization of the aggregate geometry. 13,24 It appears that the process of planarization is required a priori to enable the intermolecular interaction.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][24][25][26] For these polymers, the process of aggregation upon cooling was found to proceed in three distinct phases, i.e. (i) a swelling up and planarization upon cooling,…”
Section: Quantum Chemical Calculationsmentioning
confidence: 99%
“…It was shown that the absorption and emission spectra, as well as the excited-state properties, are strongly determined by the intrachain polymer conformation and by interchain aggregation. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Conjugated polymers can be synthesised with ionic side-chains, yielding conjugated polyelectrolytes (CPEs), which combine the optoelectronic properties of p-conjugation in the backbone with solubility in highly polar solvents and the electrostatic behaviour of polyelectrolytes. 23 CPEs provide the unique opportunity to manipulate the conformation of conjugated polymers in water and to correlate this to their photophysical behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…At 5 K in a frozen THF glass, the emission from P3HT was observed to be the superposition of two nearly identical, well-resolved spectra that differ by about 70 meV in the position of their origin. [49] Comparison with X-ray data showed that these two emissions can be assigned to two different structures. [53] In both arrangements, the chain backbones are planar and π-stacked in the same way, so that there is no difference between the two structures within one stack, and this is consistent with both emissions showing the same vibronic progression.…”
Section: The Intricacy Of Multichromophoric Systemsmentioning
confidence: 99%
“…[47] Alternatively, one may keep the solvent yet reduce the temperature. [48,49] Since the "quality" of a solvent depends on temperature, cooling has the same effect than using a poorer solvent. [50] When a good solution of P3HT is cooled from room temperature to, e.g., 160 K, as illustrated in Figure 10a, the absorption spectra show distinct changes.…”
Section: The Intricacy Of Multichromophoric Systemsmentioning
confidence: 99%